Budget Efficiency and Service Effectiveness in CRM Digitalization: A Study of Satpol PP DKI Jakarta - Revi Majiza Putra; Hadi Prabowo; Hyronimus Rowa; Udaya Madjid (Jurnal Perpajakan dan Keuangan Publik, 2026)
Digital transformation through the Citizen Relationship Management (CRM) system has significantly streamlined the administrative handling of public complaints within the Jakarta Provincial Civil Service Police Unit (Satpol PP). However, a high rate of recurring violations at the same locations indicates that administrative completion—marking a report as "resolved" in the system—does not always lead to the substantive resolution of problems in the field. This study examines CRM digitalization from the perspective of public service budget efficiency and effectiveness to determine how digital governance can better support long-term urban order. Using an exploratory qualitative approach and thematic analysis via NVivo software, the research identifies an "efficiency paradox". While Satpol PP achieves a high administrative resolution rate of 93.03%, budget inefficiencies persist because the current system is primarily reactive. Operational resources are frequently wasted on the repetitive deployment of personnel and vehicles to address identical, chronic violations that the system fails to mitigate through early detection. The study concludes that current digitalization remains at an administrative layer and must transform into a mitigative approach. As a primary scientific contribution, the research formulates the CRM-Mitigation Layer model. This model integrates predictive analytics and cross-agency coordination to shift the organization from reactive enforcement to proactive, data-driven budgeting. By focusing on early-warning mitigation and resolving the root causes of incidents, this model enhances public value by ensuring state resources are used for sustainable problem-solving rather than repetitive administrative tasks.